Accessing National Demand-Side Climate Change Mitigation Plan and Socio-Economic Impact in Nigeria - Udoinyang, Nathan (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2025)
This study examines the national demand-side climate change mitigation plan and its socio-economic impact in Nigeria, aiming to assess the opportunities and challenges of promoting sustainable development while reducing greenhouse gas emissions. Using a mixed-methods approach, the study combines qualitative and quantitative data to provide a comprehensive understanding of the socio-economic impacts of demand-side climate change mitigation strategies in Nigeria. The study's findings reveal that Nigeria's climate change mitigation policies and strategies have the potential to promote low-carbon economic development, reduce poverty, and improve public health. However, the study also highlights the challenges of implementing these policies, including limited funding, inadequate infrastructure, and lack of awareness and education on climate change issues. The study concludes that by promoting sustainable development and reducing greenhouse gas emissions, Nigeria can achieve its climate goals thereby contribute to global efforts to address climate change, and recommends for increased investment in renewable energy, promotion of climate-resilient agriculture, and development of climate-resilient infrastructure to reduce the impacts of climate change. The study also recommends that policymakers and stakeholders should prioritize climate change education and awareness, and promote participatory and inclusive approaches to climate change research and policy development. Overall, the study provides insights into the opportunities and challenges of promoting sustainable development and reducing greenhouse gas emissions in Nigeria, and highlights the need for a comprehensive and integrated approach to addressing climate change impacts in the country.